2001
DOI: 10.17660/actahortic.2001.552.3
|View full text |Cite
|
Sign up to set email alerts
|

Limonium Breeding: New Options for a Well Known Genus

Abstract: Limonium is a genus that is well known in international cut flower markets. There has been considerable investment in breeding new varieties over many years and the objective has been to try to incorporate traits from less well known species into new cultivars. Limonium perigrinum was hybridized with L. purpuratum and a plant with stems in excess of 60 cm selected from this cross for further development. This plant was later released under PVR as 'Chorus Magenta'. Subsequent breeding has had two aims -to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Morgan et al (2001) reported that the fertility of sterile interspecific hybrids, created by crossing L. perezii and L. sinuatum using embryo rescue techniques, was restored through oryzalin-induced somatic chromosome doubling. To the best of our knowledge, this is the only polyploidization study in Limonium, and thus far, no study has determined the optimum concentrations and/or exposure time for spindle toxin-induced chromosome doubling or provided a precise description of morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Morgan et al (2001) reported that the fertility of sterile interspecific hybrids, created by crossing L. perezii and L. sinuatum using embryo rescue techniques, was restored through oryzalin-induced somatic chromosome doubling. To the best of our knowledge, this is the only polyploidization study in Limonium, and thus far, no study has determined the optimum concentrations and/or exposure time for spindle toxin-induced chromosome doubling or provided a precise description of morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Our in vivo seed treatments with oryzalin successfully produced polyploids of L. sinuatum (Table 1). Morgan et al [19,23] produced interspecific hybrids of L. perezii and L. sinuatum and obtained allotetraploids after an oryzalin treatment of their embryos. These findings indicate that oryzalin treatment is effective for producing polyploid plants in Limonium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the genus Limonium, there are a few reports regarding chromosome doubling using polyploidizing agents [18]. Morgan et al [19] produced allotetraploids of an interspecific hybrid between L. perezii and L. sinuatum by oryzalin treatment of in vitro shoots. Mori et al [20] treated the seeds of L. bellidifolium with colchicine and obtained autotetraploids, which tended to produce wider, thicker leaves and larger flowers than diploid plants.…”
Section: Introductionmentioning
confidence: 99%